A Syntactic Analysis of Verb Phrases in Taylor Swift’s Never Grow Up Song - Meilani, Saneh; Latifah Hanum, Zulfa; Hanifah, Lutfia; Fitriani, Dini; Oktaviana, Fadilla; Komala Putri, Miftah (English Education, Linguistics, and Literature Journal, 2025)
This study analyzes the verb phrase in Taylor Swift’s Never Grow Up song. The research aims to identify and understand the structure of verb phrases used in the song, as well as their role in conveying meaning and emotion. The study employs a qualitative descriptive analysis method, with data extracted from the song lyrics. The findings reveal that the verb phrases in the song include key syntactic structures such as passive voice, phrasal verbs, causative verbs, infinitive phrases, and hypothetical structures. These results indicate that verb phrases in song lyrics function not only grammatically but also enhance the emotional message and theme of the song. This research suggests further exploration of other grammatical structures in song lyrics to enrich linguistic understanding of music.